Assessment of Psychological Symptoms and Quality of Life among Women with Urinary Incontinence - Mansour Khalifa; Mansour A. Farag; Azza M. Abd El Aziz; Shymaa S. Ali; Nabila T. Ahmed4; Ahmed M. Abbas (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2017)
Objective: Urinary incontinence (UI) is a common condition and a global health concern, the burden of this condition is greatest in developing countries of Asia, South America and Africa. The current study aims to assess and compare the psychological symptoms and quality of life (Qol) of women with UI in Assiut (Egypt) and Sana'a (Yemen).  Materials and Methods: A comparative study included 150 women from Yemen and 150 from Egypt, all of them complaining of UI. Tools used for the study were interview questionnaires included personal data, Incontinence Severity Index (ISI), which categorized UI into mild, moderate and severe, World Health Organization Qol scale and Symptoms Checklist-90-Revised (SCL-90-R).  Results: Significant differences were found between Yemeni and Egyptian women as regard psychological and social relationship domains of Qol. Yemeni women had higher percentages of depression and anxiety more than Egyptian women with statistically significant differences.  Conclusion: Both Yemeni and Egyptian women with UI showed impaired Qol and had high percentage of psychological symptoms especially among women with severe UI. Involvement of the incontinent women in behavioral and group therapy, the presence of psychiatrist in UI clinics to address the psychological effects and increase awareness of nursing staff regarding the effects of UI on the psychological condition and Qol is mandatory.